Behind The Mask: Gender, Neurodiversity and the Hidden Struggles of Adult Women with ADHD - Christiansen,Cecilie (2025)
This thesis investigates the lived experiences of women with Attention Deficit Hyperactivity Disorder (ADHD), diagnosed in adulthood in Denmark, focusing on how culturally ingrained norms and diagnostic frameworks contribute to masking behaviours, delayed recognition and systemic exclusion. The reason behind this thesis is a persistent underdiagnosis of ADHD in women and the subsequent resultant negative effects on mental health, social participation and self-perception. The under-diagnosis of women is often attributed to diagnostic tools and practices historically centered on male symptom presentations. Adopting a cultural and critical disability studies perspective, this thesis utilises theories of performativity, crip theory and the ‘chronic sick role’ to explore how normative expectations shape behavioural performances and reinforces stigma. A qualitative methodology underpins the thesis. The empirical material consists of 7 in-depth semi-structured interviews with 8 women, all diagnosed with ADHD in adulthood, supplemented by narrative analysis of podcast-episodes. These provide the empirical material to uncover the interplay between individual strategies and institutional barriers. Key findings reveal that women with ADHD engage in extensive masking to adhere to normative ideals of femininity and productivity, a practice that often delays their diagnosis. The study underscores the urgent need for reimagining institutional structures in education, healthcare and the workplace to foster a more inclusive understanding of neurodiversity. By highlighting the systemic production of disability through normative rigidity, the thesis advocates for a transformative approach that centers the voices of neurodivergent women and redefines what it means to be ‘able’.
Keywords: ADHD diagnosis; Adult women; Neurodiversity; Masking; Gender norms; Ableism; Crip Theory